Pengaruh Belanja Modal Pemerintah Provinsi terhadap Pertumbuhan Ekonomi Regional Daerah di Indonesia: Analisis Efektivitas Era SBY dan Jokowi - Herdi, Adli Gumilang; Marpaung, Debora Nurhary Grecia; Noviandani, Diva; Ramadhan, Muhammad Anugerah; Situmorang, Veronica Uly Artha (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the impact of provincial government capital expenditure on regional economic growth in Indonesia, with a particular focus on the comparative effectiveness between the administrations of Susilo Bambang Yudhoyono (20052014) and Joko Widodo (20142024). Using panel data from 34 provinces over the 20052024 period, this research employs panel regression with a fixed-effects specification and interaction tests between capital expenditure and government regimes. The results show that capital expenditure consistently exerts a positive and significant effect on regional economic growth. However, its effectiveness is found to be stronger during the Yudhoyono administration than during the Jokowi era, as indicated by a significant negative interaction coefficient in the latter period. Furthermore, the study identifies a structural shift in regional GDP levels between the two administrations and demonstrates the simultaneous significance of capital expenditure, government regime, and their interaction in influencing economic growth. The model explains 80.19% of the variation in regional GDP, while the remaining portion is driven by other factors such as private investment, international trade, and global economic conditions. These findings emphasize that although capital expenditure remains a vital instrument for fostering economic growth, its effectiveness largely depends on the quality of policy implementation and the surrounding political-fiscal context.